Paragenesis of magma chamber internal wall discovered in Oman ophiolite gabbros. (27th December 2015) - Nicolas, Adolphe; Boudier, Françoise; Mainprice, David
Abstract: A detailed study in Wadi Farah reveals a singular point in Jebel Dihm (southern Oman ophiolite). Here, we investigated some primitive features of accretion at a fast‐spreading ridge that has exceptionally been exempt from hydrous alteration while crossing the TBL (thermal boundary layer). The conjunction of two factors has made this possible in the Farah area: its location at the point of sharp foliation rotation from the upper to the transitional gabbros and a locally twisted TBL. These factors may have favoured the intrusion within the TBL of hydrous wedges transverse to the ridge. Deeper into the TBL, near the active ridge, the wedges merge and are covered by veneers of totally fresh gabbros bearing glittering acicular clinopyroxene. These gabbros are interpreted as relics of the crystallizing internal wall of the magma chamber that have interacted with hydrous fluids. This internal TBL has anisotropic thermal properties and acts as a thermal blanket, maintaining high magma‐chamber temperatures.